2007
DOI: 10.1152/ajpregu.00495.2007
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid status affects 5-HT2Areceptor modulation of breathing before, during, and following exposure of hamsters to acute intermittent hypoxia

Abstract: Varney AA, Schlenker EH. Thyroid status affects 5-HT2A receptor modulation of breathing before, during, and following exposure of hamsters to acute intermittent hypoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…In some cases thyroid hormone therapy reverses these dysfunctions, but not always (Jha et al, 2006; Misiolek et al, 2007). At the molecular level, thyroid hormones affect the expression and phosphorylation of various enzymes and the expression of pumps, channels and neurotransmitter systems that may affect ventilation including opioids, serotonin, gamma amino butyric acid, and dopamine (Burton and Kazemi, 2000; Diez et al, 2008; Kulikov and Zubkov, 2007; Sarkar et al, 2006; Schlenker, 1994; Slotkin and Slepetis, 1984; Varney and Schlenker, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…In some cases thyroid hormone therapy reverses these dysfunctions, but not always (Jha et al, 2006; Misiolek et al, 2007). At the molecular level, thyroid hormones affect the expression and phosphorylation of various enzymes and the expression of pumps, channels and neurotransmitter systems that may affect ventilation including opioids, serotonin, gamma amino butyric acid, and dopamine (Burton and Kazemi, 2000; Diez et al, 2008; Kulikov and Zubkov, 2007; Sarkar et al, 2006; Schlenker, 1994; Slotkin and Slepetis, 1984; Varney and Schlenker, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…The advantage of using an agent such as PTU is that it can be administered in drinking water at various concentrations that may induce different levels of hypothyroidism (Goodman and Gilbert, 2007). Moreover, this is a method that has been used previously in our laboratory in hamsters (Varney and Schlenker, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…For example, Schlenker and coworkers showed PTU-induced hypothyroidism in hamsters depressed the stimulatory effects of naloxone, a mu-opioid receptor antagonist, on ventilation (Schlenker, 1994). More recently, Varney and Schlenker reported that a specific serotonin 2A receptor antagonist (R)-(+)-α-(2,3-dimethoxyphenyl)-1-[2-(4-fluorophenyl)ethyl]-4-piperidinemethanol (MDL 100907) resulted in long-term depression of ventilation (a decrease in ventilation following intermittent hypoxia relative to baseline values) in euthyroid, but not in hypothyroid hamsters (Varney and Schlenker, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Hypothyroidism also affects the respiratory system and control of breathing (Duranti et al, 1993) and (see references (Schlenker, 2012; Schlenker et al, 1994)). Several studies from our laboratory indicate that hypothyroidism specifically affects modulation of breathing by altering the function of various neurotransmitter systems and receptors including opioids, serotonin and dopamine (Schlenker et al, 1994; Schlenker and Schultz, 2011a; Varney and Schlenker, 2007). …”
Section: 0 Introductionmentioning
confidence: 99%